Adsorption of an organochlorine pesticide using activated carbon produced from an agro‐waste material. Issue 12 (4th December 2013) - Seyhi, Brahima; Drogui, Patrick; Gortares‐Moroyoqui, Pablo; Estrada‐Alvarado, María I.; Alvarez, Luis H.
Abstract BACKGROUND Activated carbon was prepared from wheat straw generated by intensive agricultural activities in the Yaqui Valley (northwest of Mexico), and was used as adsorbing material for heptachlor removal from aqueous solution. Adsorption experiments were carried out in batch mode in order to evaluate the effects of pH, activated carbon concentration and heptachlor concentration on the adsorption process. RESULTS The adsorption of heptachlor reached efficiencies higher than 97% under neutral and acidic conditions. Increasing the activated carbon concentration from 1 g L−1 to 2 g L−1 promoted an increase in adsorption efficiency of heptachlor from 92% to 97%. The Langmuir isotherm for heptachlor removal resulted in adsorption rate constant KL = 20.8 L g−1 and maximum adsorption capacity qm = 2.22 mg g−1. The pseudo‐second‐order model describes the heptachlor adsorption kinetic, giving a value of 0.3135 g mg−1 min−1. CONCLUSION Wheat straw was used to produce activated carbon for the removal of heptachlor. The use and application of wheat straw for this purpose could be one of the responses to eradicate the problems associated with its incineration. The activated carbon produced showed good adsorption capacity for heptachlor. © 2013 Society of Chemical Industry